2002
DOI: 10.1111/j.1365-2621.2002.tb08809.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Feta Cheese Made Using Different Cultures as Determined by Confocal Scanning Laser Microscopy

Abstract: The objective of this work was to observe the microstructure of feta cheese using confocal scanning laser microscopy. Low fat cheese and cheese containing capsule-producing cultures were made. The protein network was observed using the reflectance mode of the confocal microscope. Fat was stained by Nile red dye diluted with whey. More even distribution of fat with a larger number of smaller globules was observed in cheese made with noncapsule-forming culture compared to that made with the capsule-forming cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
3
11
0
1
Order By: Relevance
“…1). Our experiments support that Nile Red is a suitable dye for the localisation of hydrophobic lipids such as triacylglycerols by CLSM, as previously reported (Hassan, Frank, & Corredig, 2002;Lopez et al, 2007;Wendin, Langton, Caous, & Hall, 2000).…”
Section: Simultaneous Localisation Of Polar Lipids Glycolipids and Gsupporting
confidence: 69%
“…1). Our experiments support that Nile Red is a suitable dye for the localisation of hydrophobic lipids such as triacylglycerols by CLSM, as previously reported (Hassan, Frank, & Corredig, 2002;Lopez et al, 2007;Wendin, Langton, Caous, & Hall, 2000).…”
Section: Simultaneous Localisation Of Polar Lipids Glycolipids and Gsupporting
confidence: 69%
“…Other than Mozzarella cheeses in which studies have been done with EPS producing cultures include Feta (Hassan, Frank, & Corredig, 2002) and Karish, an Egyptian acid-coagulated cheese (Hassan, Corredig, Frank, & Elsoda, 2004). Feta is more similar to Panela than other cheeses in which the use of EPS producing cultures has been studied, since it is soft, high in moisture and fat; Hassan et al (2002) reported that the use of an exopolysaccharide slowacid-producing St. thermophilus strain resulted in the formation of large pores and fat globules in low fat Feta cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic observations are, however, limited by the resolution that can be achieved and therefore images can only be viewed at relatively low magnifications. Confocal microscopy has been used to study microstructure of dairy products by several authors (Auty, Twomey, Guinee, & Mulvihill, 2001;Hassan, Frank, & Corredig, 2002;Hassan, Frank, Farmer, Schmidt, & Shalabi, 1995).…”
Section: Introductionmentioning
confidence: 99%